Hubungan Iklim Organisasi dengan Organizational Citizenship Behavior Guru SMAN 1 Ujung Batu - Pratiwi, Fony; Rinaldi, Rinaldi (JFACE: Journal of Family, Adult, and Early Childhood Education, 2020)
Teachers. This study aims to determine the relationship of organizational climate with organizational citizenship behavior (OCB) teachers at SMAN 1 Ujung Batu. The design of this study was quantitative correlational, with the population in this study were all of the teachers of SMAN 1 Ujung Batu. The sampling technique used was total sampling, with a total of 48 research subjects. Data collection was carried out using the scale of organizational climate and the scale of organizational citizenship behavior (OCB). The analysis technique used is the product moment correlation test. The results showed a significant positive relationship between organizational climate scale and organizational citizenship behavior (OCB) with rxy = 0.967 with p = 0,000 (p <0.01) which means that the higher the organizational climate, the better organizational citizenship behavior ( OCB). Then the lower the organizational climate, the more it is not very good organizational citizenship behavior (OCB)